Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.1 - Simplifying Rational Expressions - Exercise Set: 65

Answer

answer is correct -3-x

Work Step by Step

answer is correct -3-x becouse $\frac{9-x^{2}}{x-3}$= $\frac{3^{2}-x^{2}}{x-3}$= $\frac{(3-x)(3+x)}{-(3-x)}$= $\frac{(3+x)}{(-1)}$=-(3+x)=-3-x
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.